E-NTPDases: Possible Roles on Host-Parasite Interactions and Therapeutic Opportunities - Paes-Vieira, Lisvane; Gomes-Vieira, André Luiz; Meyer-Fernandes, José Roberto (Frontiers in Cellular and Infection Microbiology, 2021)
Nucleoside triphosphate diphosphohydrolases (NTPDases) are enzymes that belong to the GDA1/CD39 protein superfamily. These enzymes catalyze the hydrolysis of ATP and ADP to the monophosphate form (AMP) and inorganic phosphate (Pi). Biochemical characterization of the nucleotidases/NTPDases from various types of cells, including those from plants, animals, and pathogenic organisms, has revealed the existence of several isoforms with different specificities with respect to divalent cations (such as calcium and magnesium) and substrates. In mammals, the NTPDases play important roles in the regulation of thrombosis and inflammation. NTPDases have been identified on the surface of several parasites, such as Trypanosoma sp, Leishmania sp., Trichomonas vaginalis, Toxoplasma gondii and Schistosoma sp. In parasites, these enzymes have shown to be involved in parasite growth, infectivity and virulence. Experimental evidence has suggested that the regulation of ATP and adenosine levels by parasite NTPDases can modulate the host immune response. In this review, we provide an overview of recent works that show not only the involvement of the nucleotidases/NTPDases in parasites infectivity and virulence, but also how inhibition of NTPDases contributes to parasite clearance and the development of new antiparasitic drugs.